The Influence of Service Quality and Price on the Interest of Commuterline KRL Passengers - Waode Utari Nur Aisyah; Fahruddin Salim; Mohammad Sofyan (Yayasan Ilomata, 2019)
This electric train transportation facility is a means of transportation that avoids traffic congestion because it has its own route. Transportation competition can be seen through aspects of service quality to transportation service providers. The excellence of the company can be demonstrated by providing good quality service and striving for affordable ticket prices by the public. This study aims to determine and analyze the effect of Service Quality and Prices on Commuterline KRL Passenger Interest. This study used 125 respondents who used the commuterline train at Tanjung Priok station. This study used a quantitative method with multiple linear regression analysis taking data by distributing questionnaires. Sampling in this study using nonprobability sampling techniques. The results of the analysis partially and simultaneously show that service quality and price affect the interests of passengers.